Synaptotagmin-1 attenuates myocardial programmed necrosis and ischemia/reperfusion injury through the mitochondrial pathway - Teng Sun; Jialei Li; Shuang Wang; Yu Han; Xiangyu Tao; Min Yuan; Zhijie Jing; Ting Liu; Yuehong Qi; Siqi Liu; Yanlin Feng; Jiasong Chang; et al. (Cell Death and Disease)
Abstract Programmed necrosis/necroptosis greatly contributes to the pathogenesis of cardiac disorders including myocardial infarction, ischemia/reperfusion (I/R) injury and heart failure. However, the fundamental mechanism underlying myocardial necroptosis, especially the mitochondria-dependent death pathway, is poorly understood. Synaptotagmin-1 (Syt1), a Ca2+ sensor, is originally identified in nervous system and mediates synchronous neurotransmitter release. The later findings of Syt1 expressions in many non-neuronal tissues including muscles suggest that Syt1 may exert important functions beyond regulation of neurotransmitter release. Syt1 is highly expressed in cardiomyocytes and has been used as an extracellular molecular probe for SPECT imaging of cardiac cell death in acute myocardial infarction. However, whether Syt1 functions in the pathogenesis of cardiac disorders and what is the molecular etiology have not yet been clarified. We showed here that Syt1 expression was significantly down-regulated in mice I/R injured heart tissues, H2O2-challenged cardiomyocytes and hypoxia/reoxygenation (H/R)-damaged cardiomyocytes. Enforced expression of Syt1 significantly inhibited myocardial necrotic cell death and interstitial fibrosis, and improved cardiac function in mice subjected to I/R operation. In exploring the underlying mechanisms, we found that Syt1 interacted with Parkin and promoted Parkin-catalyzed CypD ubiquitination, thus inhibited mitochondrial membrane permeability transition pore (mPTP) opening and ultimately suppressed cardiomyocyte necrosis. We further found that Syt1 expression was negatively regulated by miR-193b-3p. MiR-193b-3p regulated cardiomyocyte necrosis and mPTP opening by targeting Syt1. Our present work revealed a novel regulatory model of myocardial necrosis composed of miR-193b-3p, Syt1, Parkin, and CypD, which may provide potential therapeutic targets and strategies for heart protection.